Self-assessment based on language learning outcomes: a study with first year engineering students - Durán Escribano, Pilar; Pierce McMahon, Joana (Alicante Journal of English Studies / Revista Alicantina de Estudios Ingleses, 2010)
As the Bologna Process moves forward, changes in European systems of higher education are expected. The introduction of the ECTS focussing on the students’ achievements described in terms of the learning outcomes and competences acquired is one of the innovations. This process, encouraged by Universidad Politécnica de Madrid, signifies a change in teaching focus, from an input model to an output one, which promotes self-assessment in a flexible curriculum, in this case adapted to student’s language profile. To illustrate this new approach in language learning, a pilot experience with Technical English mining engineering students is discussed, with special attention to learner reflection and self-assessment practices. Students’ progress in self-assessment, based on the introduction of learning outcomes in specific language courses, is analysed to conclude that personal engagement and clear purpose -specified in terms of learning outcomes- seem to have become relevant components to student's self-assessment practice.